Leptin Inhibit the Effect of Pioglitazone in Reducing MMP-9 and MMP-13 of IL-1β-Induced Chondrocytes - Rena Normasari; Anis Murniati (Journal of Agromedicine and Medical Sciences, 2015)
Osteoarthritis (OA) is the most common cause of joint pain, but there’s still no satisfying treatment that can inhibit degradation of articular cartilage in OA. One approach that is being widely studied is through activation of PPAR-γ. Many studies have shown effect of PPAR-γ on OA either in vitro or in vivo in animal model. On the other hand, the main risk factor of OA is obesity. Obesity generally followed by increased of leptin level due to leptin resistance. The aim of this study is to examine the effect of pioglitazone as PPAR-γ agonist in reducing the level of MMP-9 and MMP-13 in OA chondrocyte with hyperleptinemia. MMP-9 and MMP-13 are key role enzymes that degrades cartilage in OA. This study use IL-1β-induced chondrocyte exposed to pioglitazone. Pioglitazone 0,1μM, 1μM, and 10μM reduce MMP-9 and MMP-13 level. Whereas pioglitazone together with leptin 10μg/ml reduce the decrease level of MMPs compared to the group without leptin. Leptin inhibit the effect of pioglitazone in reducing the level of MMPs.Keywords: OA, leptin, pioglitazone, MMP-9, MMP-13